The AhR pathway is dysregulated in alopecia areata - Arno Belpaire; Annelies Demeyer; Elise Van Caelenberg; Nanja van Geel; Reinhart Speeckaert (Journal of Translational Autoimmunity)
Despite significant progress in the treatment of alopecia areata (AA), many aspects of its immune-based pathogenesis remain unexplored. IFN-γ, primarily produced by CD8+ T cells and NK cells, is considered central to AA pathogenesis. However, the complex immune signaling network contributes to therapeutic resistance and frequent disease flares after treatment discontinuation. The aryl hydrocarbon receptor (AhR) pathway, upregulated by IFN-γ, modulates Th17 responses, but its inhibitory effects on IFN-γ remain unclear. Although IL-17 levels are elevated in AA, clinical trials indicate that IL-17A inhibitors are ineffective. AhR expression is known to induce immune checkpoints (ICPs) such as PD-1, suggesting a potential role as a negative feedback mechanism. This study investigated AhR expression in lymphocytes from AA patients and its association with clinical and laboratory markers of disease activity. AhR expression was significantly reduced in CD4, CD8, Th1, and Th17 lymphocytes in AA patients compared to healthy controls (p < 0.005), and it correlated inversely with SALTII scores (p < 0.05). ROC analysis showed that AhR levels in CD8 cells could differentiate mild AA from healthy controls with a sensitivity of 82.35 % and specificity of 86.84 %, suggesting potential diagnostic utility. Lower AhR levels were associated with increased IFN-γ+ lymphocytes and decreased IL-17+ immune cells. Interestingly, immune profiles differed between atopic and non-atopic patients: in severe AA, higher AhR expression was linked to increased sPD-1 concentrations, whereas in limited AA, AhR failed to upregulate any investigated ICP. These findings highlight the significant downregulation of the AhR pathway in AA and suggest its potential as a therapeutic target. Future research should explore the development of AhR agonists or antagonists to modulate immune responses in AA.